2022
DOI: 10.1002/med.21890
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic landscape of SHP2 provides molecular insights for SHP2 targeted drug discovery

Abstract: The protein tyrosine phosphatase SHP2 encoded by PTPN11 is a promising therapeutic target for cancer therapy. The dynamic change of SHP2 between closed and open conformations under either physiological or pathological conditions provides opportunities to design SHP2 inhibitors for treating SHP2-related diseases. To date, several SHP2 allosteric inhibitors have advanced into clinical trials as mono-or combined therapy of cancers. In this review, we provide an overview on the structural landscape of SHP2 under p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 76 publications
0
21
0
2
Order By: Relevance
“…Tumour tissue samples will then help to reliably identify a tumour subtype and possible molecular targets when surgery had failed. Indeed, a variety of targeted therapies were already developed for the gene product of the PTPN11, such as orthosteric inhibition of the SHP2 protein [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour tissue samples will then help to reliably identify a tumour subtype and possible molecular targets when surgery had failed. Indeed, a variety of targeted therapies were already developed for the gene product of the PTPN11, such as orthosteric inhibition of the SHP2 protein [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the investigation of the correlation between ZBTB9 and KRAS signaling pathway demonstrated that ZBTB9 was evidently associated with MAPK1, NRAS, SHP2, SOS1, and KRAS2 (all play imperative roles in KRAS pathway [38][39][40]), suggesting that the malignant biological behaviors under ZBTB9 upregulation were probably mediating through this pathways. Blocking of ZBTB9 could have the potential value to optimize the efficacy of inhibitors against KRAS signaling pathways [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Shp2 keeps an auto-inhibited close conformation with intramolecular interaction between the N-SH2 and PTP domain under the basal state. Binding of a phosphotyrosine-containing peptide to the N-SH2 domain results in a conformational change to relieve this auto-inhibition ( Neel et al, 2003 ; Song et al, 2022 ). In our study, we found that α-actinin-4 may either directly or indirectly interact with the Shp2 at FAs.…”
Section: Discussionmentioning
confidence: 99%